Hyperkalemia and Renin–Angiotensin–Aldosterone System Inhibitors Dose Therapy in Heart Failure With Reduced Ejection Fraction - Giuseppe MC Rosano; Ilaria Spoletini; Cristiana Vitale; Stefan Agewall (Cardiac Failure Review)
Renin–angiotensin–aldosterone system inhibitors (RAASi) are known to improve outcomes in patients who have heart failure with reduced ejection fraction (HFrEF). To reduce mortality in these patients, RAASi should be uptitrated to the maximally tolerated dose. However, RAASi may also cause hyperkalemia. As a result of this side-effect, doses of RAASi are reduced, discontinued and seldom reinstated. Thus, the therapeutic target needed in these patients is often not reached because of hyperkalemia. Also, submaximal dosing of RAASi may be a result of symptomatic hypotension, syncope, hypoperfusion, reduced kidney function and other factors. The reduction of RAASi dose leads to adverse outcomes, such as an increased risk of mortality. Management of these side-effects is pivotal to maximise the use of RAASi in HFrEF, particularly in high-risk patients.